Growth factor and galaxy bias from future redshift surveys: a study on parametrizations - Di Porto, Cinzia; Amendola, Luca; Branchini, Enzo (Monthly notices of the Royal Astronomical Society, 2011)
Many experiments in the near future will test dark energy through its effects on the linear growth of matter perturbations. In this paper, we discuss the constraints that future large-scale redshift surveys can put on three different parametrizations of the linear growth factor and how these constraints will help ruling out different classes of dark energy and modified gravity models. We show that a scale-independent bias can be estimated to a few per cent per redshift slice by combining redshift distortions with power spectrum amplitude. We find that the growth rate can be constrained to within 2-4 per cent for each Δz= 0.2 redshift slice, while the equation of state w and the index γ can be simultaneously estimated both to within 0.02. We also find that a constant dimensionless coupling between dark energy and dark matter can be constrained to be smaller than 0.14.